The effects of predicted environmentally relevant concentrations of ZnO nanoparticles on the behavior of Gallus gallus domesticus (Phasianidae) chicks - Mesak, Carlos; Sampaio, Douglas Marcel dos Reis; Ferreira, Raíssa de Oliveira; Mendes, Bruna de Oliveira; Rodrigues, Aline Sueli de Lima; Malafaia, Guilherme (Environmental pollution (1987), 2018)
The toxicity of ZnO nanoparticles (NPs) has been the subject of several investigations; however, concentrations much higher than the ones potentially found in the environment are often tested. In addition, groups of animals such as birds have not been used as model in studies in this field, fact that creates an important ecotoxicological gap in them. The aim of the present study is to investigate the effects of the exposure to environmentally relevant concentrations of ZnO nanoparticles on the anti-predatory behavior of chicks (Gallus gallus domesticus). The test animals were daily exposed to an environmentally relevant concentration of ZnO nanoparticles (0.245 mg kg−1) and to a toxic concentration of it (245.26 mg kg−1) through intraperitoneal injection for two days. We set a control group for comparison purposes. According to our results, ZnO nanoparticles did not affect the locomotor activity of, and did not cause anxiolytic or anxiogenic effect on, birds in the open field test. However, based on the lowest cluster score recorded during the social aggregation test, chicks exposed to ZnO nanoparticles failed to recognize the grunt of a hawk (Rupornis magnirostris) as predatory threat. Only birds in the control group recognized the test snake (Pantherophis guttatus) as potential predator. The higher Zn concentration in the brains of animals exposed to ZnO nanoparticles evidenced the capacity of these nanomaterials to cross the blood–brain barrier, even at low concentrations. This blood-brain barrier crossing could have affected the structures or neuronal mechanisms that modulate the defensive response of birds. Assumingly, even the minimal exposure to low concentrations of ZnO nanoparticles can affect birds. Our outcomes corroborate previous studies about the biological risks of water surface contamination by metal-based nanomaterials. [Display omitted] •ZnO nanoparticles influences Gallus gallus domesticus behavior.•Birds exposed to the ZnO NPs not recognize the snake as potential predatory.•ZnO NP interferes with hawk's recognition as a potential predator.